2021
DOI: 10.1038/s41398-021-01631-0
|View full text |Cite|
|
Sign up to set email alerts
|

APOE4 genotype exacerbates the depression-like behavior of mice during aging through ATP decline

Abstract: Population-based studies reveal that apolipoprotein E (APOE) ε4 gene allele is closely associated with late-life depression (LLD). However, its exact role and underlying mechanism remain obscure. The current study found that aged apoE4-targeted replacement (TR) mice displayed obvious depression-like behavior when compared with age-matched apoE3-TR mice. Furthermore, apoE4 increased stress-induced depression-like behaviors, accompanied by declines in the hippocampal 5-HT (1A) radioligand [18F] MPPF uptake evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 67 publications
(66 reference statements)
2
14
0
Order By: Relevance
“…Human studies have consistently documented lower CMRglc in subjects possessing one or more APOE ε4 gene, even at early ages (Reiman et al, 1996;Reiman et al, 1998;Small et al, 1995). An age-dependent reduction in glucose transport into the CNS has been reported in the ApoE-TR lines used here (Alata et al, 2015;Fang et al, 2021), though this was reported to occur at ages (8-12 months) far beyond most of the mice we examined. Surprisingly, another ApoE4-expressing model exhibits elevated CMRglc as it progresses into advanced ages (Kotredes et al, 2021).…”
Section: Discussionmentioning
confidence: 66%
“…Human studies have consistently documented lower CMRglc in subjects possessing one or more APOE ε4 gene, even at early ages (Reiman et al, 1996;Reiman et al, 1998;Small et al, 1995). An age-dependent reduction in glucose transport into the CNS has been reported in the ApoE-TR lines used here (Alata et al, 2015;Fang et al, 2021), though this was reported to occur at ages (8-12 months) far beyond most of the mice we examined. Surprisingly, another ApoE4-expressing model exhibits elevated CMRglc as it progresses into advanced ages (Kotredes et al, 2021).…”
Section: Discussionmentioning
confidence: 66%
“…In our study, the ATP5O level significantly reduced and, accordingly, ATP levels also significantly decreased under CS. The correlation of reduced ATP level with abnormal metabolism has been reported [36,37,46]; however, details regarding how the metabolism is altered are still lacking. Our quantitative crotonyl-omics demonstrated that the crotonylation level of ATP5O decreased the most and much more than another ATP synthase subunit, Atp5f1a, indicating that the decrotonylation activity of HDAC2 has good preference for ATP5O.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, ATP5O decrement will significantly decrease the function of ATP synthetase and reduce the cytoplasmic energy level, as verified within CS oocytes (Figure 2(p)) and liver (Figure 3(a)). Because it has been reported that decreased cytoplasmic energy level could cause abnormal metabolism [36,37], we sent plasma samples for fullspectrum metabolomics (Figure 3(b)). At a threshold of CS/control ≥ 1.5 or ≤0.67, there were 435 downregulated and 189 upregulated metabolites, and the downregulated metabolites covered 69.71% of all metabolites (Figures 3(c) and 3(d)).…”
Section: Phospholipid Metabolism Was Downregulated In Csmentioning
confidence: 99%
“…Preclinical evidence suggests that APOE isoform modulates cerebral glucose uptake but with unclear directionality. Reports of increased brain glucose uptake (Venzi et al, 2017) are contradicted by decreased CNS‐wide glucose uptake following dietary/cognitive challenge (Johnson et al, 2019) or environmental stress in aged E4‐TR mice (Fang et al, 2021). Further, young E4‐TR mice demonstrated impaired brain glucose metabolic rate which was rescuable with rapamycin treatment, which also reduced CypA expression (Lin et al, 2017), hinting at a potential conserved target between the APOE4 ‐mediated vascular impairment (Hit 2), neuroinflammation (Hit 3) and metabolic disruption (Hit 6).…”
Section: Hit 6: Lipid and Cellular Metabolism Disruptionmentioning
confidence: 99%
“…ApoE4 fragments accumulate in the mitochondria and ER, impairing mitochondrial complex function and inducing cellular toxicity. Abbreviations: ApoE4, apolipoprotein E4; GLUT4, glucose transporter 4; IDE, insulin degrading enzyme; PPARy, peroxisome proliferator-activated receptor y.Created with BioRender.com (Johnson et al, 2019) or environmental stress in aged E4-TR mice (Fang et al, 2021). Further, young E4-TR mice demonstrated impaired brain glucose metabolic rate which was rescuable with rapamycin treatment, which also reduced CypA expression (Lin et al, 2017), hinting at a potential conserved target between the APOE4-mediated vascular impairment (Hit 2), neuroinflammation (Hit 3) and metabolic disruption (Hit 6).…”
Section: Apoe4 Disrupts Normal Glucose Metabolismmentioning
confidence: 99%